Age-related differences in risk factors, clinical characteristics, and outcomes for intracerebral hemorrhage - Chen, Chu; Xie, Yanfang; Pu, Mingjun; Deng, Lan; Li, Zuoqiao; Yang, Tiannan; Yin, Hao; Zhang, Zhehao; Lv, Xinni; Liu, Xueyun; Cheng, Jing; Li, Qi (Frontiers in Aging Neuroscience, 2023)
Background and purpose: Intracerebral hemorrhage (ICH) is a severe form of stroke that remains understudied in the young adults. We aimed to investigate the clinical presentation, and risk factors associated with ICH in this age group and compare them to older patients. Methods: Our study included ICH patients admitted between March 2016 and December 2021 in the First Affiliated Hospital of Chongqing Medical University from our ongoing prospective cohort database. Demographic characteristics, etiology, risk factors, and clinical outcomes were compared between elderly and young patients. Furthermore, logistic regression analysis was employed to explore risk factors associated with the functional outcome at 3-months. Results: We selected 1003 patients (mean age, 59.9 ±13.8 years old), 746 (74.4%) patients were aged >50 years. The logistic regression analysis showed young patients have a higher proportion of secondary ICH, higher white blood cell count and higher body mass index (BMI), but less diabetes mellitus. Of all patients, predictors of 3-month functional independence was first-ever ICH and age ≤50 years. The history of nephropathy and stroke, higer baseline NIHSS score, larger hematoma volume, and the presence of hydrocephalus were associated with poor outcomes. And the white blood cell count could significantly influenced the prognosis among young ICH patients.Three-month functional outcome based on modified Rankin scale score was better in young patients than the elderly (OR,1.232; 95%CI,1.095-1.388; p<0.001). Conclusions: The highest incidence of ICH occurs in the age groups of 50-59 and 60-69. ICH in young adults had higher white blood cell and BMI compared to the elderly, and differs in etiological distribution. The young patients also had similar short-term mortality but more favorable functional outcomes than the elderly.Furthermore, NIHSS score and larger hematoma volumes were associated with poor outcome in all patients.